Emerin interacts with histone methyltransferases to regulate repressive chromatin at the nuclear periphery - Marano, Nicholas; Holaska, James M. (Frontiers in Cell and Developmental Biology, 2022)
X-Linked Emery-Dreifuss muscular dystrophy is caused by mutations in the gene encoding emerin. Emerin is an inner nuclear membrane protein important for repressive chromatin organization at the nuclear periphery. Myogenic differentiation is a tightly regulated process characterized by genomic reorganization leading to coordinated temporal expression of key transcription factors, including MyoD, Pax7, and Myf5. Emerin was shown to interact with repressive histone modification machinery, including HDAC3 and EZH2. Using emerin-null myogenic progenitor cells we established several EDMD-causing emerin mutant lines in the effort to understand how the functional interaction of emerin with HDAC3 regulates histone methyltransferase localization or function to organize repressive chromatin at the nuclear periphery. We found that, in addition to its interaction with HDAC3, emerin interacts with the histone methyltransferases EZH2 and G9a in myogenic progenitor cells. Further, we show enhanced binding of emerin HDAC3-binding mutants S54F and Q133H to EZH2 and G9a. Treatment with small molecule inhibitors of EZH2 and G9a reduced H3K9me2 or H3K27me3 throughout differentiation. EZH2 and G9a inhibitors impaired cell cycle withdrawal, differentiation commitment, and myotube formation in wildtype progenitors, while they had no effect on emerin-null progenitors. Interestingly, these inhibitors exacerbated the impaired differentiation of emerin S54F and Q133H mutant progenitors. Collectively, these results suggest the functional interaction between emerin and HDAC3, EZH2, and G9a are important for myogenic differentiation.